Reagan : the life - Brands, Henry W., 1953- 1953- (Doubleday, 2015)
"Ronald Reagan today is a conservative icon, celebrated for transforming the American domestic agenda and playing a crucial part in ending communism in the Soviet Union. In his masterful new biography, H. W. Brands argues that Reagan, along with FDR, was the most consequential president of the twentieth century. Reagan took office at a time when the public sector, after a half century of New Deal liberalism, was widely perceived as bloated and inefficient, an impediment to personal liberty. Reagan sought to restore democracy by bolstering capitalism. In Brands's telling, how Reagan, who voted four times for FDR, engineered a conservative transformation of American politics is both a riveting personal journey and the story of America in the modern era. Brands follows Reagan as his ambition for ever larger stages compelled him from a troubled childhood in small-town Illinois to become a radio announcer and then the quintessential public figure of modern America, a movie star. In Hollywood, Reagan edged closer to public service as the president of the Screen Actors' Guild, before a stalled film career led to his unlikely reinvention as the voice of General Electric and a spokesman for corporate America. Reagan follows its subject on his improbable political rise, from the 1960s, when he was first elected governor of California, to his triumphant election in 1980 as president of the United States. Brands employs archival sources not available to previous biographers and dozens of interviews with surviving members of the administration. The result is an exciting narrative and a fresh understanding of a crucially important president and his era"..